2020
DOI: 10.3390/ijms21082990
|View full text |Cite
|
Sign up to set email alerts
|

A Novel CD147 Inhibitor, SP-8356, Attenuates Pathological Fibrosis in Alkali-Burned Rat Cornea

Abstract: The corneal fibrotic responses to corneal damage often lead to severe corneal opacification thereby resulting in severe visual impairment or even blindness. The persistence of corneal opacity depends heavily on the activity of corneal myofibroblast. Myofibroblasts are opaque and synthesize a disorganized extracellular matrix (ECM) and thus promoting opacification. Cluster of differentiation 147 (CD147), a member of the immunoglobulin superfamily, is known to play important roles in the differentiation process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…For example, a clinically approved CD147-monoclonal antibody, Meplazumab could potentially block viral entry. A recent small molecule CD147 inhibitor was reported that reduces corneal fibrosis in a rat model of alkali burn [ 17 ]. Azithromycin, approved use in the US and global markets as AzaSite may act to block CD147 [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a clinically approved CD147-monoclonal antibody, Meplazumab could potentially block viral entry. A recent small molecule CD147 inhibitor was reported that reduces corneal fibrosis in a rat model of alkali burn [ 17 ]. Azithromycin, approved use in the US and global markets as AzaSite may act to block CD147 [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…In regards to direct ocular infection, CD147 has been critically shown to be expressed in the retina as well as the ocular surface [ 15 ]. CD147 has been shown to be upregulated in ocular surface disease [ 16 , 17 ]. For this reason, the use of silicone punctal plugs or intracanalicular plugs may dually block transport of virus from the ocular surface to the highly susceptible nasal epithelium, but could also act to optimize the ocular surface thereby reducing relative expression of CD147.…”
Section: What Are the Molecular Mechanisms By Which The Sars-cov-2mentioning
confidence: 99%
“…CD147 is well established as an MMP inducer (57-59) and has been shown to have multifunctional roles in many progressive diseases and in animal models of disease (28)(29)(30)(31), including, cardiovascular disease, Alzheimer's and more recently as an entry route into cells for SARs-CoV-2 (COVID 19) (60-62). Its involvement in CKD has been well described (32,33) and in the supplementary data (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Using SP-8356 an inhibitor of CD147, topically on rat corneas that had undergone alkali burns, inhibited αSMA expressing myofibroblasts and other fibrotic associated ECM components such as collagen and MMP9 (29). Basigin (bsg)+/mice had less cardiac interstitial fibrosis following transverse aortic constriction compared to control mice.…”
Section: Introductionmentioning
confidence: 99%
“…Topical administration of EMMPRIN inhibitor, SP-8356, suppressed the myofibroblast population and the deposition of abnormal ECM products (e.g. MMP9, Col3, and Col5) in a rat model of corneal alkali injury, hence reducing corneal haze and fibrosis (Joung et al, 2020). Moreover, green tea polyphenol epigallocatechin-3-gallate (EGCG), was reported to restrain EMMPRIN and MMP-9 expression via 67-kD laminin receptor pathway in a PMA-induced macrophage system (Wang et al, 2016).…”
Section: Recombinant Proteins and Inhibitorsmentioning
confidence: 99%